A Comparison Between the Effects of Image-Schema and Data-Driven Teaching on Learning English Prepositions by Intermediate Kurdish EFL Learners - Ahmed Azeez Mohammed; Fatemeh Mirzapour; Nesa Nabifar (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The objective of the current study was to observe the efficiency of Image schema and Data-Driven Teaching methods in helping intermediate Kurdish students in learning six English prepositions, which were in, on, at, to, behind, in front of, between, besides, over and under. The participants of the study were 100 intermediate EFL Kurdish learners aged 18 to 20 from Lebanese French University in Kurdistan, Iraq. The participants were two groups, first experimental and second experimental groups (50 in each group). The present research adopted a quantitative study as quasi-experimental research fulfilled in the form of pretest and a posttest. The uniformity of the EFL students was ensured using the Oxford Placement Test (OPT). The researcher created the pretest and posttest in this study to assess the participants' learning and retention before and after the intervention. The results revealed that Image schema group had a greater impact on English preposition learning in comparison with Data-Driven Teaching group. Thus, this study has some academic effects for English language teachers in Iraq to be aware of cognitive linguistic usage as a frequent practice in the EFL classroom.